The Iban Folk Belief - Noria, Tugang; Anna, Durin; Yow, Chong Lee; Hashim, A; Adilawati, A; Bibiana Motey, anak Bilon@Senang (Human Resource Management Academic Research Society (HRMARS), 2018)
This paper aims to examine Iban’s miring tradition using Victor Turner’s (1985) theoretical framework of sociodrama. Miringis a worship presentation by providing food to extraordinary powers consisting of god, goddess, good spirit and evil spirit, and their ancestors' spirit that have died long ago in order to seek for solution to the problems they encountered in their daily life. In other words, miring is part of Iban’s folk belief system passed down from one generation to another. By incorporating Turner’s sociodrama, it gives new perspective on miring ritual as a form of sociodrama, of which mantra and ritual dance are performed with many other ingredients prepared alongside the ritual. Symbols that signify Iban people’s life is very much interconnected with their environment and the supernatural world are recorded and given meanings in this article.